Frailty in an older population : the impact on community-dwelling elders, dementia patients and older caregivers - Ní Mhaoláin, Áine (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2012)
Frailty represents one of the greatest gerontological challenges faced by societies in coming years. Growing numbers of older citizens leads not only to increasing numbers of healthy elders, but also frail and disabled elders.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin